Macrophage migration inhibitory factor rejuvenates aged human mesenchymal stem cells and improves myocardial repair - Zhang, Yuelin; Zhu, Wenwu; He, Haiwei; Fan, Baohan; Deng, Rui; Hong, Yimei; Liang, Xiaoting; Zhao, Hongyan; Li, Xin; Zhang, Fengxiang (Aging (Albany, NY.), 2019)
The beneficial functions of mesenchymal stem cells (MSCs) decline with age, limiting their therapeutic efficacy for myocardial infarction (MI). Macrophage migration inhibitory factor (MIF) promotes cell proliferation and survival. We investigated whether MIF overexpression could rejuvenate aged MSCs and increase their therapeutic efficacy in MI. Young and aged MSCs were isolated from the bone marrow of young and aged donors. Young MSCs, aged MSCs, and MIF-overexpressing aged MSCs were transplanted into the peri-infarct region in a rat MI model. Aged MSCs exhibited a lower proliferative capacity, lower MIF level, greater cell size, greater senescence-associated-β-galactosidase activity, and weaker paracrine effects than young MSCs. Knocking down MIF in young MSCs induced cellular senescence, whereas overexpressing MIF in aged MSCs reduced cellular senescence. MIF rejuvenated aged MSCs by activating autophagy, an effect largely reversed by the autophagy inhibitor 3-methyladenine. MIF-overexpressing aged MSCs induced angiogenesis and prevented cardiomyocyte apoptosis to a greater extent than aged MSCs, and had improved heart function and cell survival more effectively than aged MSCs four weeks after MI. Thus, MIF rejuvenated aged MSCs by activating autophagy and enhanced their therapeutic efficacy in MI, suggesting a novel MSC-based therapeutic strategy for cardiovascular diseases in the aged population.